2006
DOI: 10.1097/01.jom.0000233380.13087.37
|View full text |Cite
|
Sign up to set email alerts
|

Community Exposure to Perfluorooctanoate: Relationships Between Serum Levels and Certain Health Parameters

Abstract: No toxicity from PFOA was demonstrated using the measured end points; other end points need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
162
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 45 publications
10
162
4
2
Order By: Relevance
“…As shown in Supplementary Table S3, previous studies have investigated the associations between serum lipids and PFAAs concentrations (Emmett et al, 2006;Sakr et al, 2007a;Sakr et al, 2007b;Frisbee et al, 2010a;Nelson et al, 2010;Eriksen et al, 2013;Fisher et al, 2013). However, those data are not always consistent.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As shown in Supplementary Table S3, previous studies have investigated the associations between serum lipids and PFAAs concentrations (Emmett et al, 2006;Sakr et al, 2007a;Sakr et al, 2007b;Frisbee et al, 2010a;Nelson et al, 2010;Eriksen et al, 2013;Fisher et al, 2013). However, those data are not always consistent.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, Olsen et al conducted a study among 506 fluorochemical production workers and showed no association between PFOA and TC or LDLC . Emmett et al (2006) assessed PFOA concentrations among 371 residents living around a DuPont plant and found no association between PFOA and TC. Results from Canadian Health Measures Survey exhibited an association between PFOA and TC in unweighted models, but this association became insignificant after weighting for sampling strategy (Fisher et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Neither a worker population study (Kaplan 2004) nor a community-based PFOA-exposed population (Emmett et al 2006a, b) has reported associations between PFOA and hepatic clinical chemistries. In the Emmett et al (2006a) study, there was no relationship between the blood levels of PFOA and the results for cholesterol, hepatic-related tests (serum protein, albumin, bilirubin, serum alkaline phosphatase, AST, ALT and GGT), or being treated for or informed by a physician that a community participant had liver disease (cirrhosis, hepatitis, and any other liver condition).…”
Section: Discussionmentioning
confidence: 99%
“…In another occupational study, Kaplan (2004) did not report an association between HDL and serum PFOA concentrations. Neither did Emmett et al (2006a) in a community-based exposure study whose median PFOA concentrations (approximately 0.354 lg/ml) were 60 times higher than that of general population studies (Calafat et al 2006;Olsen et al 2003b). To further clarify any possible association with HDL, the A apolipoproteins, which form the major proteins found in HDL, could be measured although this was not part of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[89][90][91] In some cases, water treatment using activated carbon has been shown to be effective for removing longer chain PFAs such as n-PFOA from contaminated source waters. [20,[54][55][56]70] PFAs, like their hydrocarbon fatty acid analogs, [92,93] also sorb to inorganic surfaces such as sands, clays, iron oxides, calcium fluoride, and surface modified silicas. [82,94,95] but organic matter sorption is thought to be dominant in most environmental systems and offer the most promising for treatment methods.…”
Section: Introductionmentioning
confidence: 99%